Group hypnosis for stress reduction and improved stress coping: a multicenter randomized controlled trial - Silvia Fisch; Suzana Trivaković-Thiel; Stephanie Roll; Theresa Keller; Sylvia Binting; Margit Cree; Benno Brinkhaus; Michael Teut (BMC Complementary Medicine and Therapies, 2020)
Abstract Background The aim of the trial was to investigate the effect of a hypnotherapeutic group program in healthy persons with increased levels of perceived stress. Methods In a randomized controlled multicenter trial participants with a self-assessed subjective stress level ≥ 40 mm on a visual analogue scale (0–100 mm; VAS) for the previous week and a stable state of health were randomized to either 5 weekly sessions of 120-min duration of a hypnotherapeutic group program for stress reduction and improved stress coping plus 5 hypnosis audiorecords for individual practice at home plus an educational booklet for stress coping (hypnosis group) versus an educational booklet only (control group). The primary outcome parameter was the VAS stress level for the previous week after 5 weeks. Secondary outcome parameters included the VAS stress level after 12 weeks, perceived stress (CPSS), depression (ADS-K), self efficacy (SWE) and quality of life (SF 36) after 5 weeks and 12 weeks. Analysis of covariance with a significance level of 5% using the full analysis set was used for analysis; the model included treatment (fixed effect), VAS baseline value (fixed covariate), and center (random effect). Results A total of 95 participants were randomized; 47 (40 female, 45 ± 13.4 years of age) were allocated to the hypnosis group, and 48 (41 female, 46.9 ± 14.3 years) were allocated to the control group. Regarding VAS stress level after 5 weeks, the adjusted VAS mean in the hypnosis group was 41.8 mm [95% confidence interval (CI): 35.2; 48.4] compared to 62.9 mm [56.2; 69.7] in the control group, and the group difference was − 21.2 mm [− 30.1; − 12.2] (P < 0.001). After 12 weeks, the stress intensity on the VAS showed a between-group difference of − 14.7 mm [− 25.1; − 4.4] (P = 0.006), and the adjusted means were 41.1 mm [33.4; 48.8] in the hypnosis group and 55.9 mm [48.4; 63.5] in the control group. Improvements were also reported for CPSS, SF-36, SWE and ADS-K after 5 and 12 weeks. Conclusion Compared to the control group, the hypnosis group showed reduced perceived stress after 5 and 12 weeks. Trial registration ClinicalTrials.gov NCT03525093 ; date of registration: May 15, 2018.